2019
DOI: 10.1109/jeds.2019.2923204
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Inhomogeneity of Schottky Diode on Nonpolar AlN Grown by Physical Vapor Transport

Abstract: An aluminum nitride (AlN) Schottky barrier diode (SBD) was fabricated on a nonpolar AlN crystal grown on tungsten substrate by physical vapor transport. The Ni/Au-AlN SBD features a low ideality factor n of 3.3 and an effective Schottky barrier height (SBH) of 1.05 eV at room temperature. The ideality factor n decreases and the effective SBH increases at high temperatures. The temperature dependences of n and SBH were explained using an inhomogeneous model. A mean SBH of 2.105 eV was obtained for the Ni-AlN Sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
1
24
2
Order By: Relevance
“… is the barrier height, and A ∗ is the effective Richardson constant (~57.6 Acm −2 K −2 for AlN) [ 16 ]. The temperature effect on I on /I off ratio of the fabricated device is shown in Figure 3 e, where I off , I on is the diode current measured at −5V and +5V bias respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… is the barrier height, and A ∗ is the effective Richardson constant (~57.6 Acm −2 K −2 for AlN) [ 16 ]. The temperature effect on I on /I off ratio of the fabricated device is shown in Figure 3 e, where I off , I on is the diode current measured at −5V and +5V bias respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Annealing as a means of reducing the number of oxygen vacancies improves the rectification ratio, response speed and sensitivity of AlN based photodetectors [ 15 ]. Schottky barrier diodes (SBDs) have simple structures to form and yet they can be the basis for complicated device structures such as junction barrier Schottky (JBS) diodes and various types of transistors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the diode, the presence of the SnS2 interlayer and SnO interface may causes multi-surface polarity and also increases surface roughness with consist of crystal domain boundaries. Thus, these effects may cause the inhomogeneity of the SBH (Zhou et al, 2019). On the other hand, Zhou et al have shown that the peak of bent conduction band increases with increasing forward-bias and shifts away from interface region towards the semiconductor (Zhou et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, these effects may cause the inhomogeneity of the SBH (Zhou et al, 2019). On the other hand, Zhou et al have shown that the peak of bent conduction band increases with increasing forward-bias and shifts away from interface region towards the semiconductor (Zhou et al, 2019). Furthermore, these changes cause an increase in effective SBH with more uniform interface.…”
Section: Methodsmentioning
confidence: 99%
“…Wurtzite aluminum nitride (AlN) has attracted extensive attention for optical and electronic applications [1,2]. AlN holds promise for high-temperature applications and high-power devices due to its high thermal conductivity, high critical electric field and wide bandgap energy applications [3][4][5][6]. Many methods have been exploited to realize the heteroepitaxial growth of AlN, including hydride vapor phase epitaxy (HVPE), metalorganic chemical vapor deposition (MOCVD), molecular beam epitaxy (MBE), and physical vapor technique (PVT) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%